The Maui effect - Ackerman, Sara (Mira, 2024)
'Iwa Young, a field biologist dedicated to protecting her rainforest home from a proposed Eco Resort, finds her focus tested when Dane Parsons, a big wave surfer, offers to help her cause, despite her rule against dating surfers. Their evolving relationship unfolds amidst thrilling surf adventures from Maui to Portugal.